AESTHETIC VALUES OF RUINS: A CASE STUDY OF THE MALABAR RADIO STATION AREA - Rahmadean Alifani Purwatiana; Sri Handayani (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2022)
Relics of the past that have historical value must be preserved, but due to war and natural factors, these relics only leave ruins, so the conservation measures are different from buildings. The aesthetic value is one of the reasons for maintaining the ruins as they are, where this value is related to the physical and non-physical aspects of the ruins. One of the locations of the historical ruins is the ruins in the Malabar Radio Transmitting Station Area located on Mount Puntang, Banjaran District, Bandung Regency, West Java, which used to be a Radio Station complex that bridged long-distance communications between Indonesia and the Netherlands, has important historical value and impact the time. A change in function to become a tourist spot at this location can intervene in the ruins by adding or developing tourist facilities that can reduce or damage their historical and aesthetic values. This study intends to examine the aesthetic value of the ruins of the Malabar Radio Station to find a value that can be maintained as it is. This research uses qualitative research methods by searching historical data through primary and secondary sources. The results of the study found that the aesthetic value of the ruins consisted of 1) physical aesthetic values related to the shape of the ruins that can be observed and felt with the five senses, identified forms and materials (traces of weathering, the remaining walls, and floors) that blend into the mountainous landscape to give it an interesting and distinctive landscape character and visual appeal; and 2) non-physical aesthetic value related to the function of marking the passage of time, evidence of representation of the involvement of indigenous workers, defense of independence in the Banjaran region, and becoming a tourist attraction. Both of these aesthetic values are things that must be protected and maintained for the preservation of the ruins.